Strange angels eaudiobook - St. Crow, Lili (Strange Angels,, 2009)
Lili St. Crow won accolades and an impressive readership for her Dante Valentine series. With Strange Angels, St. Crow pens a YA tale sure to raise hackles and wake the dead. Dru Anderson is a very special girl- even if she doesn't always feel it. Gifted with "the touch," Dru travels about with her dad, hunting all manner of things that go bump in the night. But then her dad turns up dead-or, er, undead-and everything changes.